Cirsium Japonicum DC ingredients-loaded silk fibroin nanofibrous matrices with excellent hemostatic activity. (16th February 2018) - Ma, Linlin; Zhang, Dongdong; Yang, Xingxing; Zhang, Lin; Chu, Jin; Kai, Guoyin; He, Chuanglong; Mo, Xiumei; Wang, Hongsheng
Abstract: Regenerated Silk fibroin (SF) from Bombyxmori has emerged in recent years as candidates for wound dressing due to its excellent biocompatibility and low inflammatory response. Cirsium Japonicum DC (CJDC) is a kind of Chinese herb medicine with evident hemostatic and anti-inflammatory analgesic effect. In this study, we aimed to manufacture a novel green electrospun SF nanofibrous matrice loading ingredients extracted from CJDC which should be useful in hemostasis as well as wound healing. FTIR spectra showed that the CJDC extracts were successfully loaded into the SF nanofibrous matrices, which appeared morphology of porous mesh structure. The as-prepared matrices inherited the good skin affinity and hemocompatibility of SF, as indicated by the skin cell viability assay and hemolysis test in vitro . Furthermore, according to the results of plasma recalcification profiles test, the incorporation of CJDC extracts significantly improved the hemostatic performance of SF nanofibrous matrices. Interestingly, the SF nanofibrous matrices loading CJDC components extracted by petroleum ether (peE-CJDC@SF) showed the best antihemorrhagic activity among the tested samples (with astringent time of 9.5 min), even better than some clinically used products such as absorbable gelatin sponge (AGS) and aseptic hemostyptic gauze (AHG). Our findings suggested the peE-CJDC@SF nanofibrous matrices could be a promising candidate using as hemostatic material and wound dressing.